Focusing on the emergencies or on their roots? The role of nonprofit organisations in immigration policymaking in Italy. Issue 1 (2nd January 2016) - Scotto, Angelo
ABSTRACT: Religious organisations are a relevant actor in immigration policymaking in Italy; they usually work in networks with institutions and other actors from the nonprofit sector to implement projects and services for migrants. However, the collaboration might lead to disagreement on which is the best way to face social problems related to immigration. In the province of Foggia, the reports on the precarious conditions of migrants employed in agriculture led to the development of a range of activities for improving their status and fighting their exploitation. While an issue network on the receipt and first assistance for migrants has arisen, there is no agreement on deeper interventions between nonprofit organisations (NPOs) which want to provide help for migrants in actual situations of precariousness and NPOs committed to face the causes of these situations. The tension between these two conceptions of nonprofit role in public policies might be divisive inside the religious associationism.